PENGARUH PENAMBAHAN GARAM TERHADAP KARAKTERISTIK DAN PENERIMAAN KONSUMER FILLET ASAP PATIN (Pangasius hypophthalmus) - Tomy Andri Zulpa; Bustari Hasan; Desmelati ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This research was intended to evaluate the effect of salt concentration onquality characteristics and consumer acceptance of smoked catfish. Two groups offish (fillet and whole eviscerated) were submerged into saturated brine solutions(30% w/v) for 0, 5, 15, 30, and 60 minutes until the fish meat contained 0%,0,92%, 1,46%, 2,52% and 3,33% salt respectively. The fish then were hot-smokedin smoke-house for 9 hours. The smoked fish were evaluated for product yield,chemical composition, sensory quality and consumer acceptance. Product yield,moisture and fat of the smoked fish decreased and protein composition increasedas the salt concentration increased. Smoked fish with 0,92% salt concentration hasthe best sensory quality and consumer acceptance. Moisture, protein, fat andproduct yield pf the best quality smoked fish were 12,54%, 27,45%, 26,33% and38,49% respectively.Keywords: Pangasius hypophthalmus, smoked catfish, salt concentration,product yield, sensory quality, chemical composition, consumeracceptance